A passage to India - Forster, E. M. (Edward Morgan), 1879-1970. (San Diego : Harcourt Brace Jovanovich, 1989)
The story about the clash between Eastern and Western cultures during British rule in India.
New York Times.
Wilson's Fiction.
Wilson's Senior High School.
Adult
Keywords: Race relations -- Fiction; India -- Social conditions -- Fiction; Political fiction